1995
DOI: 10.1111/j.1365-2222.1995.tb01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the menstrual cycle on skin‐prick test reactions to histamine, morphine and allergen

Abstract: The purpose of this study was to examine the possible influence of the phases of the menstrual cycle on dermal reactivity to skin-prick testing. We studied 15 atopic, menstruating women with seasonal rhinoconjunctivitis and/or asthma, with known sensitivity to olive and parietaria (mean age 25.2 years) and 15 non-atopic, healthy, female controls (mean age 24.7 years). Skin-prick tests with histamine, morphine, and in the atopic group with parietaria/and/or olive, were repeated three times during the same menst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 22 publications
4
38
0
1
Order By: Relevance
“…Ultrastructural and histochemical examinations show squamous metaplasia of the nasal mucosa in these patients [5,12]. Skin test reactivity in the menstrual cycle shows that the wheal-flare reactions are significantly increased in the mid-cycle when oestrogen levels reach their peak [13], which accords with the nasal hyperreactivity found in this study. One can speculate why oestrogen results in an increased sensitivity to histamine; a downregulation of cortisol receptors in nasal mucosa caused by high serum levels of oestrogen?…”
Section: Discussionsupporting
confidence: 80%
“…Ultrastructural and histochemical examinations show squamous metaplasia of the nasal mucosa in these patients [5,12]. Skin test reactivity in the menstrual cycle shows that the wheal-flare reactions are significantly increased in the mid-cycle when oestrogen levels reach their peak [13], which accords with the nasal hyperreactivity found in this study. One can speculate why oestrogen results in an increased sensitivity to histamine; a downregulation of cortisol receptors in nasal mucosa caused by high serum levels of oestrogen?…”
Section: Discussionsupporting
confidence: 80%
“…Kalogeromitros et al [20] observed that environmental and metabolic factors such as menstrual cycle could affect test reactivity [20]. Consistent with findings reported elsewhere [21], a pilot study performed by our group showed that measurement of wheal size is reproducible, with a low coefficient of variation at histamine concentrations of 10 mg/mL and 100 mg/mL during follow-up in a control group (data not shown).…”
Section: Discussionsupporting
confidence: 79%
“…However, several studies have suggested that female sex hormones influence asthma (41). Atopy, measured by skin-prick test, changes during the menstrual cycle (42). When estrogen levels are high, wheal and flare responses increase (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Atopy, measured by skin-prick test, changes during the menstrual cycle (42). When estrogen levels are high, wheal and flare responses increase (42)(43)(44). The proliferation of peripheral blood monocytes to pokeweed mitogen is increased in the presence of estrogen, whereas testosterone inhibits this response (45,46).…”
Section: Discussionmentioning
confidence: 99%